(3QSGdI CMeO GdHcGj Edi Cgd eQGcTs - (3CMeO GdHcGjs
(3ChdgG (B:s
(3CJJ bHd eG CHQC GdaLQ aRGM HgG MLQ hRGd dgG gLQ s
(3BNQgG (B:s
(3ef Gddjd MJi ajg bO jWdY GdaLQ s
(3GdfSNI HgG MhGTs
(3eUOQ GbJfGA GdCUd (B:s
(3GdeZQH (B- (3GdQHGW (B(D 206) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs